Investigation of laser assisted ultra-high frequency induction deposition method: Processes, fluid flow, and microstructure characteristic - Rui Sun; Yongjun Shi; Xiaogang Wang; Yankuo Guo; Xiaoyu Zhou (Journal of Materials Research and Technology, 2020)
In this study, a laser assisted ultra-high frequency (UHF) induction deposition method is proposed. The proposed method uses UHF induction heat as the main heat source to melt the deposited metal. A laser beam is used as the auxiliary heat source to produce a local high temperature on the substrate surface, ensuring an effective bonding between the deposited layer and the substrate. Experiments are conducted to validate the feasibility of the method. Results show that the deposited layer can be successfully prepared using the proposed method. With proper combination of process parameters, the deposited layer with low dilution rate can be obtained, which indicates a low heat input for the substrate. A numerical model is developed to investigate the variation of flow behavior and mass transport during deposition with respect to the varying current intensities. Results show that with increasing current intensity, the flow velocity in the molten pool is improved and the mass transport between deposited layer and substrate is enhanced consequently. The simulated element distribution matches with the electron dispersive spectroscopy detection results. The microstructure characteristic of the deposited layer is analyzed on the basis of the calculated solidification parameters in the solid–liquid interface. The microstructure evolution with current intensity is also predicted in accordance with the variation of the calculated solidification parameters, which indicates that the microstructure in the bottom region tends to be coarse with the decreasing current intensity. The experimental observations are consistent with the numerical prediction.